High resolution FTIR spectroscopy of fluoroform 12CHF3 and critical analysis of the infrared spectrum from 25 to 1500 cm−1; Molecular Physics; Vol. 116, iss. 9 - Albert S. Sieghard; Bekhtereva E. S. Elena Sergeevna; Bolotova I. B.; Hollenstein Hans H. A.; Quack M. Martin; Ulenekov (Ulenikov) O. N. Oleg Nikolaevich (2018, 2018)
Title screen